INTUITIONISTIC FUZZY SETS IN UP-ALGEBRAS: UP-algebra - Kesorn, Bodin; Maimun, Khanrudee; Ratbandan, Watchara; Iampan, Aiyared (Italian Journal of Pure and Applied Mathematics, 2015)
The concept of intuitionistic fuzzy sets was first introduced by Atanassov, which is a generalization of the concept of fuzzy sets. In this paper, we apply the concept of intuitionistic fuzzy sets to UP-algebras. The notions of intuitionistic fuzzy UP-ideals and intuitionistic fuzzy UP-subalgebras of UP-algebras are introduced and their basic properties are investigated. Upper t-(strong) level subsets and lower t-(strong) level subsets are derived from some intuitionistic fuzzy sets.